siRNAs targeting icaD Gene of Staphylococcus aureus to Inhibit Biofilm Formation: Structural Analysis and Efficacy - Dinda Ananda Sulistina; Rian Ka Praja; Margaretha Yayu Indah Anugerahny; Hanasia Hanasia; Ysrafil Ysrafil (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Antibiotic resistance in Staphylococcus aureus infections, especially those involving biofilm formation, is a global health issue. Biofilm protects bacteria from the immune system and antibiotic treatment, making them 10 to 1000 times more resistant. The icaD gene, part of the ica operon, is crucial for biofilm synthesis by enhancing the enzymes responsible for forming the biofilm matrix. The icaD gene sequence of Staphylococcus aureus was obtained from the GenBank NCBI database with the accession code CP140612.1, with a gene sequence length of 306 bp and employed several bioinformatics methods, including siDirect for designing and evaluating effective siRNA sequences to select the most promising candidates. Additionally, siRNA Scales, MaxExpect, Duplex Fold, and siPred were employed to analyze the siRNA sequence length, secondary structure, binding energy, and efficacy predictions of siRNAs targeting the icaD gene. The study found that out of 54 siRNA candidates, siRNA22, siRNA50, and siRNA25 achieved inhibition rates of 93.69%, 92.82%, and 92.52%, respectively. These results bioinformatically demonstrated their potential to suppress the expression of the icaD gene and highlight their promise as siRNA-based antibacterial therapies to combat biofilm-related infections. The designed siRNA computationally shows potential as an innovative therapy to combat biofilm infections caused by Staphylococcus aureus.